Costa Rican meme account admins (mememakers) and digital political participation: a qualitative study of the 2022 presidential elections - Obando Reyes, Fernando J. (2026)
This article examines the role of internet meme accounts and their administrators (mememakers) as elements of digital political participation during the 2022 general elections in Costa Rica. Based on a qualitative approach centered on case studies and in-depth interviews with six mememakers responsible for three active accounts on digital platforms (Los Memes de Mi Tía Panchita, Memenoticias, and Shitposter’s Guide 2 Costa Rica), the study explores their motivations, practices, and modes of involvement in the electoral process. Findings identify four key motivations: the need for spaces for humor, indignation toward the national sociopolitical context, the desire to inform through memes, and the exercise of freedom of expression. Additionally, the study highlights six forms of political participation enabled by these accounts: creation of political content, collaboration among accounts, dissemination of user-submitted materials, discussion of electoral events, distribution of information, and calls for civic mobilization. The study argues that, despite their similarities and differences, the mememakers interviewed are complex subjects whose practices combine humorous, critical, and informative dimensions. These individuals operate in a digital environment shaped by anonymity and the technical limitations of social media platforms, yet they facilitate symbolic spaces with public impact. The accounts they manage function as repertoires of connective action capable of influencing the public electoral conversation. While they do not yet constitute fully articulated political communities, they show signs of progressive organization, growing collaboration, and openness to more structured forms of digital participation.